In Vivo Test of Combined Leaf Extracts of Tea Mistletoe and Mango Mistletoe on Hepatic TNF-? Levels in Wistar Rats - Nur Aziza; Nour Athiroh Abdoes Sjakoer; Ari Hayati (Biology, Medicine, & Natural Product Chemistry, 2026)
Tea mistletoe (Scurrula atropurpurea) and mango mistletoe (Dendrophthoe pentandra) are known to contain bioactive compounds with potential anti-inflammatory activity. Tumor Necrosis Factor Alpha (TNF-alpha) is a key proinflammatory cytokine whose hepatic expression can be elevated by a high-fat diet. This study aimed to investigate the effect of combined extracts of tea mistletoe and mango mistletoe and determine the most effective dose in reducing hepatic TNF-alpha levels in Wistar rats induced by a high-fat diet. An in vivo experimental design was employed using 35 male Wistar rats, randomly divided into five groups: negative control, positive control (high-fat diet), and three treatment groups receiving combined extracts at doses of 50, 100, and 200 mg/kg body weight for 37 days. Hepatic TNF-alpha levels were quantified using ELISA. The results showed that the combination of tea mistletoe and mango mistletoe extracts significantly reduced TNF-alpha levels in the liver of Wistar rats fed a high-fat diet. Among the tested doses, 200 mg/kg body weight demonstrated the greatest reduction compared to lower doses. In conclusion, the combined extracts exhibit promising anti-inflammatory effects by lowering hepatic TNF-alpha levels, with 200 mg/kg body weight identified as the most effective dose under the conditions of this study.